The Influence of the Development and Management of Sports Tourism Resources on the Emotional Experience of Human Settlements - Zhongxiang Jiang; Wenting Jiang, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
This study aims to determine how sports tourism resources' development and administration affect human settlements' emotional experience. To analyze the new influencing factors of the population change rate since the beginning of the 21st century, the first decade of the 21st century in each province and city served as the research object. Excel and SPSS statistical software were used for one-way ANOVA, multiple comparative analysis, correlation analysis, and linear regression analysis. Society, the economy, medical care, education, and the natural environment were identified as the most influential factors in human settlements by the study. The population growth factor is still dominated by the economy, but people are paying increasing attention to the environmental factor. It has been discovered that people's requirements for human settlements vary over time. Despite its considerable efforts to improve the economy, China should give more attention to non-economic factors.